Phenotypic features of vascular calcification in chronic kidney disease. (10th December 2019) - Dai, L.; Debowska, M.; Lukaszuk, T.; Bobrowski, L.; Barany, P.; Söderberg, M.; Thiagarajan, D.; Frostegård, J.; Wennberg, L.; Lindholm, B.; Qureshi, A. R.; Waniewski, J.; et al.
Abstract: Background: Patients with chronic kidney disease stage 5 (CKD5) are predisposed to vascular calcification (VC), but the combined effect of factors associated with VC was sparsely investigated. We applied the relaxed linear separability (RLS) feature selection model to identify features that concomitantly associate with VC in CKD5 patients. Methods: Epigastric arteries collected during surgery from living donor kidney transplant recipients were examined to score the histological extent of medial VC. Sixty‐two phenotypic features in 152 patients were entered into RLS model to differentiate between no – minimal VC ( n  = 93; score 0‐1) and moderate – extensive VC ( n  = 59; score 2‐3). The subset of features associated with VC was selected on the basis of cross‐validation procedure. The strength of association of the selected features with VC was expressed by the absolute value of 'RLS factor'. Results: Among 62 features, a subset of 17 features provided optimal prediction of VC with 89% of patients correctly classified into their groups. The 17 features included traditional risk factors (diabetes, age, cholesterol, BMI and male sex) and markers of bone metabolism, endothelial function, metabolites, serum antibodies and mitochondrial‐derived peptide. Positive RLS factors range from 1.26 to 4.05 indicating features associated with increased risk of VC, and negative RLS factors range from −0.95 to −1.83 indicating features associated with reduced risk of VC. Conclusion: The RLS model identified 17 features including novel biomarkers and traditional risk factors that together concomitantly associated with medial VC. These results may inform further investigations of factors promoting VC in CKD5 patients. Abstract :